2019
DOI: 10.1001/jamaneurol.2018.4304
|View full text |Cite|
|
Sign up to set email alerts
|

Utility of Neuronal-Derived Exosomes to Examine Molecular Mechanisms That Affect Motor Function in Patients With Parkinson Disease

Abstract: IMPORTANCE Exenatide, a glucagon-like peptide 1 agonist used in type 2 diabetes, was recently found to have beneficial effects on motor function in a randomized, placebo-controlled trial in Parkinson disease (PD). Accumulating evidence suggests that impaired brain insulin and protein kinase B (Akt) signaling play a role in PD pathogenesis; however, exploring the extent to which drugs engage with putative mechnisms in vivo remains a challenge.OBJECTIVE To assess whether participants in the Exenatide-PD trial ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 198 publications
(165 citation statements)
references
References 82 publications
4
159
0
2
Order By: Relevance
“…Recently, a landmark double blind placebo-controlled trial also reported similar findings with patients treated with exenatide scoring on average 3.5 points less on the MDS-UPDRS than those not treated with exenatide, following a washout period to exclude a symptomatic effect [105]. In a novel approach to assessing target engagement using brain-derived exosomes purified from serum samples, the same group showed that patients treated with exenatide had an increase in levels of Akt and mTOR protein activation during the period of drug exposure in comparison with placebotreated patients [106].…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 55%
“…Recently, a landmark double blind placebo-controlled trial also reported similar findings with patients treated with exenatide scoring on average 3.5 points less on the MDS-UPDRS than those not treated with exenatide, following a washout period to exclude a symptomatic effect [105]. In a novel approach to assessing target engagement using brain-derived exosomes purified from serum samples, the same group showed that patients treated with exenatide had an increase in levels of Akt and mTOR protein activation during the period of drug exposure in comparison with placebotreated patients [106].…”
Section: Glp-1 Receptor Agonistsmentioning
confidence: 55%
“…If any of the CV drugs have “off target” (ie, independent of their effects on glucose, blood pressure, cholesterol, etc.) beneficial effects on PD neurodegeneration, then trials must focus on single agents and/or drug classes that may share a common mechanism(s) of “neuroprotection.” The GLP‐1 receptor agonists may be interesting because of their potential neuroprotective/neurorestorative properties in a range of animal models alongside data indicating potential mechanisms through antiinflammatory effects on microglia/astrocytic processes or antiapoptotic effects through the Akt/mechanistic target of rapamycin pathway . Whether these effects are distinct or if there is overlap between the neurodegenerative and microvascular disease processes is of clear interest but not yet known.…”
Section: Next Steps For Research and Translation To The Clinicmentioning
confidence: 96%
“…The GLP-1 receptor agonists may be interesting because of their potential neuroprotective/neurorestorative properties in a range of animal models [151][152][153][154] alongside data indicating potential mechanisms through antiinflammatory effects on microglia/astrocytic processes 154 or antiapoptotic effects through the Akt/mechanistic target of rapamycin pathway. 155 Whether these effects are distinct or if there is overlap between the neurodegenerative and microvascular disease processes is of clear interest but not yet known.…”
Section: Candidate Neuroprotective Therapeuticsmentioning
confidence: 99%
“…The majority of studies have used peripheral biomarkers to proxy brain processes, relying on the assumption that peripheral and brain immune activation are correlated (or that peripheral measures are reliable indicators of central processes), which has important limitations. A recent innovation is the use of blood extracellular vesicles (EVs) enriched for neuronal origin (NEVs) as a source of biomarkers that directly reflect neuronal-specific processes [19][20][21][22][23]. Extracellular vesicles (including exosomes) are membranous particles that are continuously released by virtually all cells, including neurons [24].…”
Section: Introductionmentioning
confidence: 99%